Feline diagnostic imaging - Holland, Merrilee; Hudson, Judith A., 1949- (John Wiley & Sons, 2020)
"This book offers a comprehensive resource for imaging the feline patient, with an emphasis on the unique considerations of imaging cats. It focuses on radiology and ultrasound, with some coverage of advanced imaging such as computed tomography and magnetic resonance imaging. Incorporating more than 1750 high-quality images, it is an invaluable reference for any veterinary practitioner with a significant feline caseload. Feline Diagnostic Imaging begins with information on the radiographic evaluation of the thorax, abdomen, and musculoskeletal structures, including normal anatomy and pathology, followed by a review of common echocardiographic and abdominal ultrasound findings and abnormalities. Advanced imaging of the skull using computed tomography and magnetic resonance imaging cases of brain and spinal disease are also included. Offering a feline focus not found in other imaging books, Feline Diagnostic Imaging is an essential purchase for veterinarians wishing to improve their diagnostic imaging skills in cats. It's also an excellent guide for veterinary radiologists, and veterinary students and residents"--